2018
DOI: 10.1371/journal.pone.0203600
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-acquired colonization and infections in a Vietnamese intensive care unit

Abstract: Data concerning intensive care unit (ICU)-acquired bacterial colonization and infections are scarce from low and middle-income countries (LMICs). ICU patients in these settings are at high risk of becoming colonized and infected with antimicrobial-resistant organisms (AROs). We conducted a prospective observational study at the Ho Chi Minh City Hospital for Tropical Diseases, Vietnam from November 2014 to January 2016 to assess the ICU-acquired colonization and infections, focusing on the five major pathogens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 41 publications
4
36
0
1
Order By: Relevance
“…The decreased susceptibility of S. aureus to VAN has been reported since 1997 [26]. Our study showed that VAN was fully sensitive to MRSA, which was consistent with previous reports from many Asian countries (Vietnam, Hong Kong, Philippines, Sri Lanka, Korea, China, Thailand, Nepal, Taiwan, and India) [8,9,22,25,27,28], whereas its high doses have been recommended to maintain efficacy in other countries [29]. VAN-sensitive MRSA was reported in eight pediatric hospitals in mainland China [19], whereas reduced VAN susceptibility was found in MRSA and methicillin-sensitive S. aureus clinical strains in two adult hospitals in northeast China [30].…”
Section: Discussionsupporting
confidence: 92%
“…The decreased susceptibility of S. aureus to VAN has been reported since 1997 [26]. Our study showed that VAN was fully sensitive to MRSA, which was consistent with previous reports from many Asian countries (Vietnam, Hong Kong, Philippines, Sri Lanka, Korea, China, Thailand, Nepal, Taiwan, and India) [8,9,22,25,27,28], whereas its high doses have been recommended to maintain efficacy in other countries [29]. VAN-sensitive MRSA was reported in eight pediatric hospitals in mainland China [19], whereas reduced VAN susceptibility was found in MRSA and methicillin-sensitive S. aureus clinical strains in two adult hospitals in northeast China [30].…”
Section: Discussionsupporting
confidence: 92%
“…This was coherent with studies in Sodo, Ethiopia (41.7%) [15], Southeast China (36.6%) [33], India (54%) [42] and Vietnam (40%) [43]. However, higher level of resistance against meropenem was documented in Taiwan (73.2%) [45], Pakistan (86.4%) [35] and Saudi (81.8%) [46].The relatively lower proportion resistance against meropenem in the present study might be due to the absence of meropenem prescription practice for patients in the study hospital.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, all isolates of P. aeruginosa revealed 100% resistance against piperacillin. This was significantly higher than studies from Italy (25%) [25], Vietnam (17.7%) [43], Southeast China (12%) [33], Turkey (28.7%) [44] and Taiwan (66.8%) [45].This might be associated with differences in the number of MDR strains of P.aeruginosa and patient type. The frustrating level of resistance against piperacillin antibiotic is an alarm for treatment to be guided with antimicrobial susceptibility testing hence so far, piperacillin was not prescribed in the study area (FHRH).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…A vector is an organism that does not cause disease itself but that transmits infection by conveying pathogens from one host to another [15]. Vectors may be mechanical or biological.…”
Section: Vector-bornementioning
confidence: 99%